Comparative Evaluation of the Impact of Subacute Exposure of Smokeless Tobacco and Tobacco Smoke on Rat Testis - Aprioku, Jonah Sydney; Ugwu, Theresa Chioma (International Journal of Reproductive Medicine, 2015)
This study investigated the effects of 30-day exposure to tobacco smoke (TS), smokeless tobacco (ST), and nicotine on reproductive parameters and oxidative biomarkers in prepubertal and adult male rats. Sperm motility was reduced by 77.5 and 89.0% in TS and ST exposed prepubertal rats and 71.1 and 86.4% in adult rats, respectively. Sperm count was also reduced by 64.7 and 89.9% in prepubertal rats and 64.9 and 47.0% in adult rats, respectively. Nicotine decreased sperm motility (82.2%) and count (62.6%) in prepubertal rats but caused no effect in adult rats. There were no changes in sperm morphology; testosterone was decreased, while LH and FSH were increased in exposed rats, when compared with control. Malondialdehyde levels in testes of exposed rats were increased, and GSH, SOD, and catalase were altered. Results indicate that subacute exposure of tobacco products alters sperm characteristics in a rank order of ST > TS > nicotine, which may be linked to increase in oxidative stress in the testis.